ENCOURAGEMENT OF ACTIVITY OF BUSINESS SUBJECTS THROUGH FINANCIAL-CREDIT MECHANISMS: ADVANCED EXPERIENCES OF FOREIGN COUNTRIES (Marketing Journal, 2025)
The article examines the experience of developed countries in improving the activities of small and medium -sized businesses through financial and credit mechanisms, and analyzes the trends in its development. It also explains the essence of the measures pl anned for further implementation to stimulate the activities of small and medium -sized businesses through financial and credit mechanisms.
Keywords: Business entities; European Union; small and medium -sized businesses; financial and credit mechanisms; refinancing rate